Enhancing Performance Stability of Electrochemically Active Polymers by Vapor‐Deposited Organic Networks. (8th January 2018) - Mao, Xianwen; Liu, Andong; Tian, Wenda; Wang, Xiaoxue; Gleason, Karen K.; Hatton, T. Alan
Abstract: Performance stability of electrochemically active polymers (EAPs) remains one of the greatest and long‐standing challenges with regard to EAP‐based technologies for a myriad of energy, biomedical, and environmental applications. The performance instability of EAPs originates from their structural alteration under repeated charge–discharge cycling and/or flexing. In this work, a conceptually new "soft confinement" strategy to enhance EAP performance stability, including cyclic and mechanical, by using rationally designed, vapor‐deposited organic networks is presented. These chemically cross‐linked networks, when in contact with an electrolyte solution, turn into ultrathin, elastic hydrogel coatings that encapsulate conformally the EAP micro‐/nanostructures. Such hydrogel coatings allow easy passage of ions that intercalate with EAPs, while simultaneously mitigating the structural pulverization of the EAPs and/or their detachment from substrates. Fundamentally distinct from extensively studied "scaffolding" or "synthetic" approaches to stabilizing EAPs, this soft confinement strategy relies on a postmodification step completely decoupled from the EAP synthesis/fabrication, and enjoys the unique advantage of substrate‐independency. Hence, this strategy is broadly applicable to various types of EAPs. The proposed stability enhancement strategy is demonstrated to be effective for a range of EAP systems with differing chemical and morphological characteristics under various testing conditions (repeated charging/discharging, bending, and twisting). Abstract : "Soft confinement" approach to improved performance stability of electrochemically active polymers (EAPs) is achieved by vapor‐deposited organic networks that, when in contact with electrolyte solutions, become ultrathin hydrogels encapsulating conformally micro‐/nanostructured EAPs. By modulating precursors and vapor deposition conditions, the resulting hydrogel coatings can give suitable mesh sizes to accommodate the key species that interact with the EAPs.